Reputation Engineering in Neurology: Navigating Clinical Authority, Digital Presence, and Content Strategy in the Information Era - Riyanto Sofyan, Henry (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Background: The digital transformation in healthcare has fundamentally altered how neurologists develop and uphold their professional reputation. Although digital professionalism frameworks exist for general medical practice, approaches tailored to neurology remain underdeveloped. Objective: This narrative literature review aims to synthesize evidence exploring the intersection of clinical authority, digital professionalism, and reputation management in neurology and to develop a structured, neurology-specific conceptual framework. Methods: A narrative literature review was conducted by searching PubMed, Scopus, and Google Scholar using terms such as